Correction to: Application of new multi-objective optimization algorithm for EV scheduling in smart grid through the uncertainties - Yin, WanJun; Mavaluru, Dinesh; Ahmed, Munir; Abbas, Mazhar; Darvishan, Aida (Journal of ambient intelligence and humanized computing, 2019)
In the original publication, first author WanJun Yin’s affiliation was incorrectly added.